Arc Dance Company Review - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2002)
PALABRAS CLAVE: Arc Dance Company, Kim Brandstrup, Brothers.
Dentro del apartado "Dance Now. The Place To Be. Dance in London".